Thinner : a novel - King, Stephen, 1947-; Bachman, Richard (Pocket Books, 2025)
"Attorney Billy Halleck seriously enjoys living his life of upper-class excess. He's got it all--an expensive home in Connecticut, a loving family...and fifty extra pounds that his doctor repeatedly warns will be the death of him. Then, in a moment of carelessness, Halleck commits vehicular manslaughter when he strikes a jaywalking old woman crossing the street. But Halleck has some powerful local connections and gets off with a slap on the wrist...much to the fury of the woman's mysterious and ancient father, who exacts revenge with a single word: "Thinner." Now a terrified Halleck finds the weight once so difficult to shed dropping effortlessly--and rapidly--by the week. Soon there will be nothing left of Billy Halleck...unless he can somehow locate the source of his living nightmare and reverse what's happened to him before he utterly wastes away..."--